IMPLIKASI UTANG PAJAK BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2008 TENTANG KETENTUAN UMUM DAN TATA CARA PERPAJAKAN TERHADAP WAJIB PAJAK - Setiady, Tri (FIAT JUSTISIA, 2015)
The emergence of the tax debt based, First, Formal Doctrine. The emergence of the tax debt based on formal doctrine is a form of tax collection system based Oficial Assessment System. According to this doctrine the tax debt arose because of published the determination and tax assessment. Determination and tax assessments may include: tax collection letters, tax underpayment assessment letters, and additional tax underpayment assessment letters. Second, the emergence of tax debts based on the doctrine materil is a form system of collect a tax based on Self Assessment System. So the tax debts arise due to the tax law.Keywords: Debt Tax, the Repayment Tax Debt, Disputes Tax